Pro-Poor Land Reform A Critique - Borras, Saturnino (Studies in International Development and Globalization, 2007)
Using empirical case materials from the Philippines and referring to rich experiences from different countries historically, this book offers conceptual and practical conclusions that have far-reaching implications for land reform throughout the world. Examining land reform theory and practice, this book argues that conventional practices have excluded a significant portion of land-based production and distribution relationships, while they have inadvertently included land transfers that do not constitute real redistributive reform. By direct implication, this book is a critique of both mainstream market led agrarian reform and conventional state-led land reform. It offers an alternative perspective on how to move forward in theory and practice and opens new paths in land policy research.